Methodical approaches to identification of effective wheat genes providing broad-spectrum resistance against fungal diseases - E. S. Skolotneva; I. N. Leonova; E. Yu. Bukatich; E. A. Salina (Вавиловский журнал генетики и селекции)
Among the pathogenic complex of the common wheat there is a causal agent of leaf and stem diseases: (rusts and powdery mildew), which has economic importan ce for most of the Russian regions. We propose a methodological approach for confirmation of effec tiveness of wheat genes conferring broad-spectrum resistance to different types of fungal diseases, which integrates traditional field tests and current genotyping techniques with molecular DNA markers. The pro posed approach includes the following steps: 1) evaluating of wheat genotypes using molecular DNA markers; 2) field tests for genotypes; 3) confirma tion of effective ness of broad-spectrum resistance genes by matching field scores and data from mole cular markers. A protocol has been proposed for geno typing varieties and wheat lines using markers linked to Lr16/Sr23, Lr24/  Sr24, Lr19/ Sr25, Lr26/Sr31/Yr9/Pm8, Lr37/Sr38/Yr17 and the gene Lr34(=Sr57/Yr18/Pm38) with a pleiotropic effect. Markers to the genes Lr6Ai#2/Sr6Ai#2/Pm6Ai#2 transferred from Thinopyrum intermedium into the genomes of Russian wheat varieties and markers to a new translocation from Aegi lops spel toides with a group of genes, designated as LrAsp7/SrAsp7/PmAsp7, were tested. When evaluating the contribution of the genes (including genes located on the alien translocations) to the formation of common wheat resistance to fungal diseases, it is necessary to use an extended sample, including genotypes carrying the same group of genes in a different genetic background. In addition, recommendations are given on the terms and frequency of monitoring of fungal diseases in Western Siberia, depending on the pathogen. The methodological approach proposed in the article can be used for identification and evaluation of the efficacy of the genes determining protection of wheat from fungal diseases. This approach is applicable in the investigation of genetic collections consisting of isogenic lines, sources and donors of resistance genes, as well as in the development of wheat genotypes using marker-assisted selection.